Design and Fabrication of Automated Soap Cutting Machine (Journal of Pharmaceutical Negative Results, 2022)
The automated soap cutting machine helps the small scale industries by increasing the production rate. The soap cutting machine is fully automated which uses a lead screw mechanism for the movement of cutter and pushers. Usually by conventional method a person used to cut the soaps by manual cutters which may have disfigured shapes and do not have precise cuts. They also deal with the problem of collecting the soap bars after the cutting process. The primary objective of this project is to expand the production rate and also to have a precise cutting process. The collection of the finished products are also made easy. The microcontroller controls the motion of the cutter and pushers. The overall machine is electrically powered.